Synthesis and Antimicrobial Activities of 3-(2-Hydroxy-3-substituted-5-methyl phenyl)-5-(3,4-methylenedioxyphenyl)-2-pyrazoline and Its Derivatives - Khadsan, R.E.; Kadu, M.V.; Doshi, A.G.; Aloolkar, N.H. (Asian Journal of Chemistry, 2016)
2-Hydroxy-3-substituted-5-methyl acetophenone (Ia–c) condenses with 3,4-methylenedioxy benzaldehyde in ethanol medium in presence of NaOH to give chalcones (IIa–c). Chalcones (IIa–c) react with hydrazine hydrate in ethanol to give 1-H pyrazolines (IIIa–c). Chalcones (IIa–c) react with phenyl hydrazine in ethanol to give 1-phenyl pyrazolines (IVa–c). Similarly, chalcones (IIa–c) react with 2,4-dinitrophenyl hydrazine in ethanol to give 1-2,4-dinitrophenyl pyrazolines (Va–c). The structure were established on the basis of spectral data, IR and NMR. Antimicrobial activities of these compounds assayed against test organisms S. aureus, S. dysentariae, S. typhi, E. coli, K. pneumonie and P. mirabilis. The activities of these compounds were compared with standard drug chloram phenicol.